Association of diaphragm thickness and echogenicity with age, sex, and body mass index in healthy subjects. Issue 2 (9th June 2022) - van Doorn, Jeroen L. M.; Wijntjes, Juerd; Saris, Christiaan G. J.; Ottenheijm, Coen A. C.; van Alfen, Nens; Doorduin, Jonne
Abstract: Introduction/Aims: Diaphragm ultrasound is increasingly used in the diagnosis of diaphragm dysfunction and to guide respiratory management in patients with neuromuscular disorders and those who are critically ill. However, the association between diaphragm ultrasound variables and demographic factors like age, sex, and body mass index (BMI) are understudied. Such relationships are important for correct interpretation of normative values and comparison with selected patients groups. The aim of this study was to determine the associations between diaphragm ultrasound variables and subject characteristics. Methods: B‐mode ultrasound was used to image the diaphragm at the zone of apposition in 83 healthy subjects. Diaphragm thickness at resting end‐expiration ( T end‐exp ), diaphragm thickness at maximal end‐inspiration ( T max‐insp ), diaphragm thickening ratio ( T max‐insp / T end‐exp ), and diaphragm echogenicity were measured. Multivariate linear regression was used to explore the associations between diaphragm ultrasound variables and subject characteristics. Results: T end‐exp, T max‐insp, and thickening ratio do not change with age whereas diaphragm echogenicity increases with age. The thickening ratio had a weak negative association with BMI, while T end‐exp was positively associated with BMI. Men had a larger T end‐exp and T max‐insp than women ( T end‐exp 1.6 ± 0.5 and 1.4 ± 0.3 mm; p  = .011, T max‐insp 3.8 ± 1.0 and 3.2 ± 0.9 mm; p  = .004), but similar thickening ratios. Discussion: Diaphragm thickness, thickening, and echogenicity measured with ultrasound are associated with factors such as age, BMI, and sex. Therefore, subject characteristics should be considered when interpreting diaphragm ultrasound measurements. In the absence of normative values, matched control groups are a prerequisite for research and in clinical practice.